The mediated mind : affect, ephemera, and consumerism in the nineteenth century - Zieger, Susan Marjorie (Fordham University Press, 2018)
This book describes new affective and material modes of print media consumption that emerged in the nineteenth century, when ephemeral printed material and objects became part of everyday modern life. It offers a history of our own moment of digital absorption, information addiction, and social media obsession.
Keywords: Mass media and literature.; Mass media and culture.; Mass media -- Social aspects -- History -- 19th century.; Printed ephemera -- Social aspects -- History -- 19th century.; Médias et littérature.; Médias et culture.; Médias -- Aspect social -- Histoire -- 19e siècle.; Publications éphémères -- Aspect social -- Histoire -- 19e siècle.; SOCIAL SCIENCE -- Media Studies.; Mass media and culture; Mass media and literature; Mass media -- Social aspects; Printed ephemera -- Social aspects; 1800-1899; Electronic books.; History